Conservation of Biodiversity in Natural Forests through Preservation Plots - a Historical Perspective - Khullar, Pankaj (Indian Forester, 1992)
The conservation of biodiversity is a subject that is attracting worldwide attention today. The importance of conservation of flora and fauna had already been recognised by foresters in India as early as 1898, when the first wildlife sanctuary was established in the country. The first Preservation Plot, for preservation and study of floristics was established in Bihar In 1906. The network of Preservation Plots now numbers 309. Today, when large areas are no longer available for closure for the preservation of flora and fauna, a network of Preservation Plots, such as those already established in India, can be the solution to the problem of preservation of the animal and plant genetic resources.